Fostering Cross-cultural Competence and Reading Comprehension through Digital Shared Reading in an Indonesian EFL Classroom - Lanlan Muhria; Tabrani ZA; Vinsensia Anisa Citta Erydani; Desi Surlitasari Dewi; Mohammed Abbas Mahdi (Journal of Innovation in Educational and Cultural Research, 2025)
Reading comprehension requires linguistic proficiency and the capacity to understand and interpret cultural elements embedded in the texts. However, many EFL students struggle with cross-cultural competence, affecting their comprehension of diverse reading materials. This study investigates the effectiveness of digital shared reading in enhancing both reading comprehension and cross-cultural competence among junior high school students in Indonesia. Employing a pre-experimental pre-test post-test design, the study involved 34 students in a structured digital shared reading intervention. Data were collected through reading comprehension tests and the Cultural Intelligence Scale (CQ) by Ang and Dyne. The results, analyzed using paired sample t-tests, indicated a statistically significant improvement in reading comprehension (t = -10.539, p = .000) and cross-cultural competence (t = -14.457, p = .000) after the intervention. These findings demonstrate the potential of digital shared reading as an effective pedagogical tool to foster cross-cultural awareness and enhance reading comprehension in EFL settings. This study contributes to educational research by showcasing how digital literacy and cultural exposure can be integrated into language learning.